2020
DOI: 10.14786/flr.v8i3.489
|View full text |Cite
|
Sign up to set email alerts
|

It is all in the surv-eye: can eye tracking data shed light on the internal consistency in self-report questionnaires on cognitive processing strategies?

Abstract: Although self-report questionnaires are widely used, researchers debate whether responses to these types of questionnaires are valid representations of the respondent's actual thoughts and beliefs. In order to provide more insight into the quality of questionnaire data, we aimed to gain an understanding of the processes that impact the completion of self-report questionnaires. To this end, we explored the process of completing a questionnaire by monitoring the eye tracking data of 70 students in higher educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
(70 reference statements)
0
20
0
Order By: Relevance
“…This is particularly pressing since existing research suggests that learners tend to use ineffective learning strategies (Jamieson-Noel & Winne, 2003), and do not make effective use of available resources to optimize their learning, even in those environments that build on effective learning designs (Ellis, et al, 2005;Lust, et al, 2013). As discussed in this special issue, potential reasons are students' cognitive processing capacity (Chauliac, et al, 2020), exerted effort (Iaconelli & Wolters, 2020), and student characteristics (Vriesema & McCaslin, 2020). Comparing self-reported data with online traces of learning behaviour taps right into a potential upward bias in self-reports on motivation and strategy use.…”
Section: Removing Analytical Restrictions Of Inventories On Motivatiomentioning
confidence: 99%
“…This is particularly pressing since existing research suggests that learners tend to use ineffective learning strategies (Jamieson-Noel & Winne, 2003), and do not make effective use of available resources to optimize their learning, even in those environments that build on effective learning designs (Ellis, et al, 2005;Lust, et al, 2013). As discussed in this special issue, potential reasons are students' cognitive processing capacity (Chauliac, et al, 2020), exerted effort (Iaconelli & Wolters, 2020), and student characteristics (Vriesema & McCaslin, 2020). Comparing self-reported data with online traces of learning behaviour taps right into a potential upward bias in self-reports on motivation and strategy use.…”
Section: Removing Analytical Restrictions Of Inventories On Motivatiomentioning
confidence: 99%
“…Finally, in terms of developing additional methods for testing validity, Chauliac et al (2020) observed university students' gaze behavior while answering items on a questionnaire assessing habitual use of different cognitive strategies during learning from texts. There were systematic links between number and duration of fixations, on the one hand, and the consistency of answering different items from the same scale, on the other.…”
Section: Examining the Validity Of Self-report Measuresmentioning
confidence: 99%
“…Only one study used think aloud procedures. Chauliac, et al (2020) asked participants to rate how frequently they applied various cognitive processes while studying textual information. Durik and Jenkins (2020) administered survey items calling for respondents to the degree to which they agreed with statements describing interest in several areas of study: astronomy, biology, math and psychology; and a single item inviting respondents to classify how certain they were about the set of ratings of interest.…”
Section: The Landscape Of Self-reports Represented In This Special Issuementioning
confidence: 99%
“…Examples are an experience in the immediate past, such as a just-completed session of collaborative work or a class period that has just finished. Moeller and colleagues (2020) minimized the time interval with their experience sampling method, as did Chauliac et al (2020) by administering their survey after participants had just completed a studying task. The other end of this spectrum is a generalized setting, such as studying or life in school.…”
Section: Facets Of a Self-report Datummentioning
confidence: 99%
See 1 more Smart Citation